Socio-demographic Patterns, BehaviouralPatterns, and Predominant Causes of Smoking Tobacco among Construction Workers: : A Case Study of Savar, Dhaka, Bangladesh. (Bangladesh Journal of Public Administration, 2022)
The socio-demographic patterns, behavioural patterns, and predominant causes of smoking tobacco among construction workers were explored using data from Savar, Dhaka, Bangladesh construction sites. A mixed questionnaire based on the basic socio-demographic and behavioural patterns such as sex, age, education, marital status, average monthly income, family size etc. and predominant causes of smoking such as addiction/habit, peer pressure, personal/family/occupational stress relief etc. was prepared and presented to the consenting study respondents (n=110) at Savar, Dhaka, Bangladesh. The patterns and causes were selected based on the previous literature review. Also, a Focus Group Discussion (FGD) was conducted with 11 consenting participants. The resultant data was then analysed using the OpenEpi v3.01 software (CDC, USA).Chi-square tests and logistic regression analysis (OR and 95% CI)were conducted using the software. Preliminary analysis revealed that the overall smoking prevalence in the study sample was 63.63% (n = 70).The two most significant causes of smoking in the study sample were an addiction to smoking (44.29%) and peer pressure (24.29%). Through a review of the findings of this study, it can be ascertained thatthere is a high prevalence of smoking among the construction workers of Savar, Dhaka, and behavioural patterns of smoking are associated with critical socio-demographic factors. Findings suggest the need for control on the easy availability oftobacco and intervention policies such as a ban on tobacco smoking in public places, especially construction sites, imposing of high tax and surcharge on tobacco products etc., aimed at reducing tobacco use among the construction workers of Savar, Dhaka.Keywords: Savar, tobacco, smoking, patterns, causes, construction workers.